Age- and gender-specific changes of tricuspid annular motion velocities in normal hearts. Issue 5 (May 2015) - Hayashi, Shuji; Yamada, Hirotsugu; Nishio, Susumu; Hotchi, Junko; Bando, Mika; Takagawa, Yuriko; Saijo, Yoshihito; Hirata, Yukina; Sata, Masataka
Abstract: Background: Mitral annular motion (MAM) and tricuspid annular motion (TAM) velocities obtained by pulsed tissue Doppler echocardiography have been used to evaluate left ventricular (LV) and right ventricular (RV) functions. Although TAM velocity has been clinically applied for evaluating various cardiac diseases, the effects of age and gender remain unclear. Therefore, we aimed to determine the effects of age and gender on TAM velocity in normal hearts. Methods: We randomly selected 265 subjects (mean age, 59 years; range, 20–89 years) without abnormal clinical, electrocardiographic, and echocardiographic findings from a pool of subjects who had undergone transthoracic echocardiography. They were classified into four age groups: 20–39, 40–59, 60–79, and >80 years. Pulsed wave Doppler was applied to obtain MAM velocity of the lateral side and TAM velocity of the RV free wall side. The peak systolic ( s ′), early diastolic ( e ′), and atrial systolic ( a ′) velocities of MAM and TAM were measured in all subjects. Results: While MAM- s ′ ( r = −0.267, p < 0.001) correlated with age, TAM- s ′ did not ( p = 0.755). TAM- s ′ in any age groups had no significant gender differences. TAM- e ′ ( r = −0.447, p < 0.001) and MAM- e ′ ( r = −0.724, p < 0.001) correlated with age, respectively. In those aged 40–59 years, both TAM- e ′ ( p = 0.002) and MAM- e ′ ( p = 0.048) in females were significantly higher than those in males. The gender differences diminished in the ≥60 years age groups. Conclusions: There was no age-associated decline in TAM- s ′, while TAM- e ′ varied with age and gender as did MAM- e ′. Although the same criteria for the TAM- s ′ can be used for identifying abnormal RV systolic function regardless of age and gender, age and gender differences must be considered when one utilizes the TAM- e ′ for the diagnosis or management of cardiovascular disease.